Scripture learning towards knowledge of God among the youth an integrated approach - Idos, Rodello A. (2006)
This study is an initial attempt to describe the knowledge level of students about God and to determine the relationship between scripture learning and knowledge of God through the use of Integrated Approach. It employed qualitative research. Results of the study showed that scripture learning is a significant predictor of a person's knowledge of God and that the Integrated Approach to scripture learning is effective in developing respondents' knowledge of God. The use of the approach was recommended as well as the integration of the findings of the study into values education curriculum and enhancement program and teachers' training.
Thesis (Ph.D. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Religious education -- Study and teaching -- Philippines -- Manila Metropolitan Area; Youth -- Education -- Philippines -- Manila Metropolitan Area; Values -- Philippines -- Manila Metropolitan Area